Упростите выражение Вычислите :

0 голосов
35 просмотров

Упростите выражение

\frac{5}{4+\sqrt{11}}+\frac{8}{\sqrt{19}-\sqrt{11}}-\frac{10}{\sqrt{19}+3}

Вычислите :

9^{\frac{3}{2}}+27^{\frac{2}{3}}-(\frac{1}{16})^{-\frac{3}{4}}


Алгебра (2.8k баллов) | 35 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

\frac{5}{4+\sqrt{11}}+\frac{8}{\sqrt{19}-\sqrt{11}}-\frac{10}{\sqrt{19}+3}=\frac{5(4-\sqrt{11})}{(4+\sqrt{11})(4-\sqrt{11})}+\frac{8(\sqrt{19}+\sqrt{11})}{(\sqrt{19}-\sqrt{11})(\sqrt{19}+\sqrt{11})}-\frac{10(\sqrt{19}-3)}{(\sqrt{19}+3)(\sqrt{19}-3)}=\frac{5(4-\sqrt{11})}{5}+\frac{8(\sqrt{19}+\sqrt{11})}{8}-\frac{10(\sqrt{19}-3)}{10}=4-\sqrt{11}+\sqrt{19}+\sqrt{11}-\sqrt{19}+3=4+3=7

 

9^{\frac{3}{2}}+27^{\frac{2}{3}}-(\frac{1}{16})^{-\frac{3}{4}}=9^{\frac{3}{2}}+27^{\frac{2}{3}}-16^{\frac{3}{4}}=\sqrt[2]{9^3} +\sqrt[3]{27^2} -\sqrt[4]{16^3} =\sqrt[2]{9^3} +\sqrt[3]{27^2} -\sqrt[4]{16^3} =3^3+3^2-2^3=27+9-8=28

(271k баллов)
0 голосов

вложил решение ниже.....

(4.6k баллов)